2016
DOI: 10.1155/2016/2763160
|View full text |Cite
|
Sign up to set email alerts
|

Oral Gingival Cell Cigarette Smoke Exposure Induces Muscle Cell Metabolic Disruption

Abstract: Cigarette smoke exposure compromises health through damaging multiple physiological systems, including disrupting metabolic function. The purpose of this study was to determine the role of oral gingiva in mediating the deleterious metabolic effects of cigarette smoke exposure on skeletal muscle metabolic function. Using an in vitro conditioned medium cell model, skeletal muscle cells were incubated with medium from gingival cells treated with normal medium or medium containing suspended cigarette smoke extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For insulin treatments, myotubes received 100 nM insulin (Actrapid; Novo Nordisk, Plainsboro, NJ, USA) for 10 min before harvesting. Cigarette smoke extract (CSE) was generated as previously described [ 8 ], with slight modifications. Mouse bronchial alveolar macrophages were obtained following euthanasia and exsanguination as previously outlined [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For insulin treatments, myotubes received 100 nM insulin (Actrapid; Novo Nordisk, Plainsboro, NJ, USA) for 10 min before harvesting. Cigarette smoke extract (CSE) was generated as previously described [ 8 ], with slight modifications. Mouse bronchial alveolar macrophages were obtained following euthanasia and exsanguination as previously outlined [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously found that smoke exposure disrupts metabolic function, including insulin sensitivity and mitochondrial physiology [ 5 , 6 ]. Certainly, multiple mechanisms likely exist that mediate the deleterious metabolic consequences, but the sphingolipid ceramide warrants particular attention given its well-established and robust role in the etiology of metabolic disruption [ 4 , 7 , 8 , 9 , 10 ], including that arising from cigarette smoke exposure [ 3 , 6 ]. Importantly, ceramide accrual with smoke exposure appears to be at least partially mediated through the activation of the receptor for advanced glycation end-products (RAGE) [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cells and tissue were prepared for mitochondrial respiration as described previously [9] before being transferred to respirometer chambers using the Oroboros O2K oxygraph (Oroboros, Innsbruck, Austria). Electron flow through complex I was supported by glutamate + malate (10 mM and 2 mM, respectively) to determine leak oxygen consumption (GML).…”
Section: Methodsmentioning
confidence: 99%
“…Unsurprisingly, consistent DEP inhalation is implicated with several cardiorespiratory disorders and mortality [7], with both epidemiological [8] and molecular [7] evidence indicating a primary role of the lung macrophage. At least some of the pathology associated with noxious stimuli exposure is a result of macrophage-induced cytokine release, which has been a focus of earlier work from our lab [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation